High Injection Effects on Solar Cell Performances - P. Mialhe; B. Affour; K. El-Hajj; A. Khoury (Active and Passive Electronic Components)
Experiments are performed on solar cells under concentrated sunlight in order to explore fundamental physical processes with high injection conditions. Saturation effects are observed on the cell open circuit voltage and on the extracted values of the recombination current. A large decrease of the initial decay of the transient voltage have been measured. High injection effects are shown to be correlated with the increase of recombination current in the space charge region together with an increase of the emitterbase coupling.